CULTIVATING LITERACY AND WELL-BEING: THE ATIPS AI CHATBOT FOR RAMADAN - Suciana Wijirahayu; Zahra Aulia; Emilia Roza; Eko Digdoyo (English Review: Journal of English Education, 2026)
While Artificial Intelligence (AI) has transformed English Language Learning (ELL), generic platforms often suffer from a cultural mismatch that ignores the physiological and spiritual rhythms of diverse learners. This study introduces ATIPS (Adaptive Theological Information & Physical Support), a Holistic Digital Companion designed for Muslim students. Utilizing a mixed-methods case study at a private university in South Jakarta (N=68), the research evaluates a Triple-Integration Model that synchronizes English literacy tasks with the unique demands of the Ramadan fast. The system employs Just-in-Time Adaptive Intervention (JITAI) architecture to deliver Contextualized Scaffolding, strategically shifting from high-cognitive linguistic drills in the morning to low-stakes wellness support in the afternoon. Data from surveys, interviews, and backend telemetry reveal a significant 82% engagement rate and a 69.2% increase in perceived productivity. These results indicate that ATIPS effectively mitigates the participation tax and techno stress typically associated with intensive study during ritual periods. By bridging the Affective-Linguistic Gap, ATIPS achieves Affective-Linguistic Synchrony, where academic excellence and spiritual observance become mutually reinforcing. This research provides a critical blueprint for the transition from Responsible AI to Resonant AI, advocating for digital tools that respect the Cultural Sovereignty and well-being of the global communities they serve.